2017
DOI: 10.1097/bot.0000000000000949
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporotic Thoracolumbar Fractures—How Are They Different?—Classification and Treatment Algorithm

Abstract: Osteoporotic vertebral fractures constitute at least 50% of the osteoporotic fractures that happen worldwide. Occurrence of osteoporotic fractures make the elderly patient susceptible for further fractures and increases the morbidity due to kyphosis and pain; the mortality risk is also increased in these patients. Most fractures occur in the thoracic and thoracolumbar region and are often stable. Different descriptive and prognostic classification systems have been described, but none are universally accepted.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
62
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 45 publications
1
62
0
5
Order By: Relevance
“…advised for treating OTFs in clinical routine practice, and we are unable to determine whether PV causes new symptomatic vertebral fractures and/or serious adverse events as well as an increased risk of PV in acute OTFs [9][10][11][12] . There are no severe complications due to treatment, and although PMMA leakage frequently occurs, it is always asymptomatic [13][14][15] . We observed that the radiographic outcomes of PV appeared to provide better vertebral height restoration but worse thoracolumbar kyphosis alignment.…”
Section: Discussionmentioning
confidence: 99%
“…advised for treating OTFs in clinical routine practice, and we are unable to determine whether PV causes new symptomatic vertebral fractures and/or serious adverse events as well as an increased risk of PV in acute OTFs [9][10][11][12] . There are no severe complications due to treatment, and although PMMA leakage frequently occurs, it is always asymptomatic [13][14][15] . We observed that the radiographic outcomes of PV appeared to provide better vertebral height restoration but worse thoracolumbar kyphosis alignment.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis is a skeletal disease with the characteristic feature of low bone mass leading to a micro architectural deterioration of bone. 12 This increases the risk of fracture even with a trivial injury. The clinical and radiologic appearances of fractures in the osteoporotic spine are different from those of a healthy spine.…”
Section: Discussionmentioning
confidence: 99%
“…The thoracolumbar (TL) region (T11-L3) is the most common area of spinal fractures due to its biomechanical characteristics; TL fractures account for 60-70% of spinal fractures (1,2). As the population ages, an increasing number of TL fractures accompanied with low bone mineral density (BMD) will occur, however, its treatment is controversial (3). Conservative therapy with extended periods of bed rest leads to bone loss, while open long segment pedicle screw xation causes intra-operative trauma to the para-spinal muscle, extensive blood loss and signi cant postoperative pain with loss of motion segments (4,5).…”
Section: Introductionmentioning
confidence: 99%